2008
DOI: 10.2478/s11658-008-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transport by mammary secretory cells: Mechanisms underlying transepithelial movement

Abstract: Abstract:The secretion of calcium into milk by mammary epithelial cells is a fundamentally important process. Despite this, the mechanisms which underlie the movement of calcium across the lactating mammary gland are still poorly understood. There are, however, two models which describe the handling of calcium by mammary epithelial cells. On the one hand, a model which has existed for several decades, suggests that the vast majority of calcium enters milk via the Golgi secretory vesicle route. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In addition to ER, other organelles also have a role in [Ca 2+ ] i homeostasis of the cell, and they include the mitochondrial Ca 2+ uniporter (MCU) and the Na + /Ca 2+ exchanger (NCX) of the secretory pathway Ca 2+ /Mn 2+ ATPases (SPCAs) of the Golgi [27][28][29]41]. Although the Golgi does not seem to be a place for Ca 2+ storage, it has a critical role in the intracellular vesicular trafficking and secretion of proteins together with ER and Ca 2+ [42]. It has been suggested that an increase of [Ca 2+ ] i may increase the secretion flow, which is a primary Golgi function and responsible for executing net unidirectional intracellular transport from the rough ER (RER) toward lysosomes and the cell surface [43].…”
Section: Regulatory Roles Of Ca 2+ In Cellular Functionsmentioning
confidence: 99%
“…In addition to ER, other organelles also have a role in [Ca 2+ ] i homeostasis of the cell, and they include the mitochondrial Ca 2+ uniporter (MCU) and the Na + /Ca 2+ exchanger (NCX) of the secretory pathway Ca 2+ /Mn 2+ ATPases (SPCAs) of the Golgi [27][28][29]41]. Although the Golgi does not seem to be a place for Ca 2+ storage, it has a critical role in the intracellular vesicular trafficking and secretion of proteins together with ER and Ca 2+ [42]. It has been suggested that an increase of [Ca 2+ ] i may increase the secretion flow, which is a primary Golgi function and responsible for executing net unidirectional intracellular transport from the rough ER (RER) toward lysosomes and the cell surface [43].…”
Section: Regulatory Roles Of Ca 2+ In Cellular Functionsmentioning
confidence: 99%
“…Calcium also acts as a second messenger in the GPCR signal transduction, which mediates downstream pathways. Although the transport of calcium in mammary epithelial cells has previously been studied (3,70), and the mechanisms underlying calcium transport in the lactating mammary gland are elucidated, the level of ionized calcium and its regulation in cytosol remain unclear (59). One of the G1 genes in the calcium signaling pathway, ryanodine receptor 3 (Ryr3) is an intracellular calcium release channel.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and function of mammary glands undergo adaptive changes during pregnancy and lactation under the influence of several hormones, such as insulin, glucocorticoids, growth hormone and PRL, the latter of which regulates milk production and secretion, in part, by enhancing cellular uptake of nutrient molecules and transport of various ions across the mammary epithelia (Rillema et al, 2000; Neville et al, 2002). Ca 2+ , as a major constituent of milk, is largely transported from plasma to acinar lumen via the transcellular pathway, preferentially via PMCA2 located on the apical membrane (Shennan and Peaker, 2000; VanHouten et al, 2007; Shennan, 2008). Although the mechanism of Ca 2+ uptake across the basolateral membrane is not completely understood, several investigators suggested that it was mediated by channels of the TRPC family (El Hiani et al, 2006; Guilbert et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mammary epithelial cells were able to extract a large amount of Ca 2+ from plasma to produce milk with Ca 2+ concentrations of ∼60 and ∼100 mM in rats and rabbits respectively (Shennan and Peaker, 2000; Neville, 2005; Shennan, 2008). Ca 2+ is transported into milk through the transcellular pathway by a three‐step process consisting of (i) Ca 2+ uptake at the blood‐facing (basolateral) membrane, presumably involving Ca 2+ ‐permeable TRPC (canonical transient receptor potential) channels (Nilius et al, 2007; Guilbert et al, 2008; Abramowitz and Birnbaumer, 2009); (ii) translocation of Ca 2+ from the cytoplasm into the Golgi apparatus by SPCAs (secretory pathway Ca 2+ ‐ATPases); and (iii) ATP‐dependent Ca 2+ extrusion at the apical (luminal) membrane via PMCA2 (plasma membrane Ca 2+ ‐ATPase isoform 2) (Shennan and Peaker, 2000; VanHouten et al, 2007; Shennan, 2008). However, expression profiles of such calcium transporters, particularly TRPC channels, in mammary tissues during lactation are poorly understood.…”
Section: Introductionmentioning
confidence: 99%